Sensory Evaluation of the Quality of Kaffir Lime (Citrus hystrix DC.) Leaves Exposed to Different Postharvest Treatments - Budiarto, Rahmat; Poerwanto, Roedhy; Santosa, Edi; Efedi, Darda; Agusta, Andria (Department of Agronomy and Horticulture, IPB University, 2021)
This study aimed to evaluate the sensory attributes such as aroma, color and texture of kaffir lime leaves in response to various post-harvest treatment. The hedonic test approach was conducted by inviting 70 untrained panelists on seven post-harvest treatments, i.e. (D1) post-sortation fresh leaves, (D2) pre-sortation fresh leaves, (D3) cold-storage leaves, (D4) low temperature-storage leaves, (D5) brown dry leaves, (D6) fresh leaf-flour, and (D7) brown dry leaf-flour. The result showed that most of panelist agreed that aroma was the most important quality attribute that determined the level of preference in kaffir lime leaf products. Among seven tested products, the aroma, color, texture and overall impression of D1 was the most favorite one, while D4, D5, and D7 were assessed as low preference products. This work showed the importance of sortation and cold storage to maintain consumer likeliness. The criteria for sortation were green, clean, pest-disease free, scar free, high uniformity and fresh condition of leaves. Cold-storage at -20oC maintained the color and texture of kaffir lime leaves better than low temperature storage (5oC). To make leaf flour, the use of fresh green leaves was significantly better than brown dry ones. This finding might become the baseline data for the development of kaffir lime leaf product in the future.